SISTEM INFORMASI PENJUALAN ALAT-ALAT KESEHATAN BERBASIS WEB PADA TOKO ASMARANIS STORE - Surya Ardy Pramudya (2023)
Information technology is very influential for the progress of a business. There are various ways to promote your business, one of which is by creating website sales. Asmaranis Store is a business venture engaged in sales and marketing. Where the Asmaranis Store sells various kinds of medical equipment such as masks, equipment for rapid tests, equipment for injecting infusions and medical devices. Currently, the Asmaranis Store does not have a web. Design web writer uses Visual Studio Code software by discussing PHP programming. The author hopes that web can publish information quickly so that customers have no difficulty in finding information and also on web customers can see what products are sold at the Asmaranis Store.